Quantifying maladaptation during the evolution of sexual dimorphism - Matthews, Genevieve (Proc Biol Sci, 2019)
Females and males have distinct trait optima, resulting in selection for sexual dimorphism. However, most traits have strong cross-sex genetic correlations, which constrain evolutionary divergence between the sexes and lead to protracted periods of maladaptation during the evolution of sexual dimorphism. While such constraints are thought to be costly in terms of individual and population fitness, it remains unclear how severe such costs are likely to be. Building upon classical models for the ‘cost of selection’ in changing environments (sensu Haldane), we derived a theoretical expression for the analogous cost of evolving sexual dimorphism; this cost is a simple function of genetic (co)variances of female and male traits and sex differences in trait optima. We then conducted a comprehensive literature search, compiled quantitative genetic data from a diverse set of traits and populations, and used them to quantify costs of sexual dimorphism in the light of our model. For roughly 90% of traits, costs of sexual dimorphism appear to be modest, and comparable to the costs of fixing one or a few beneficial substitutions. For the remaining traits (approx. 10%), sexual dimorphism appears to carry a substantial cost—potentially orders of magnitude greater than costs of selection during adaptation to environmental changes.